A Case Study Analysis : Conoco - Malaysia / Ahmad Fitri Ismail, Fairus Halizam A. Hamzah and Mohd. Shahril Kemis - Ismail, Ahmad Fitri; A. Hamzah, Fairus Halizam; Kemis, Mohd. Shahril (Faculty of Business and Management, 2001)
The company millions call Conoco today began 125 years ago as the Continental Oil and Transportation Co., one of the first petroleum marketers in the West. Isaac Elder Blake, Conoco's founder, observed that town's people in Ogden, Utah still used candies and whale oil to light their homes. Although kerosene was available, hauled by the case from a primitive refinery in Colorado, It was too expensive for the thrifty pioneers. Blake figured if kerosene were imported from eastern refineries by railroad tank cars and sold in bulk, prices would drop and demand would rise.